European Yearbook of International Economic Law 2018 - Bungenberg, Marc; Krajewski, Markus; Tams, Christian J.; Terhechte, Jörg Philipp; Ziegler, Andreas R. (European Yearbook of International Economic Law, 2019)
XVII, 524 p.